Construction of knowledge on facebook - Idris, Hayati; Abdul Ghani, Rozina (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study highlights a segment of a larger study that explores the discourse of social network sites. These social sites such as Twitter, Facebook and Myspace have become such an intriguing social media that there is a growing need among educationalists to explore their impact in the field of teaching and learning. In Malaysia, Facebook is one of the most popular social network sites. Therefore, this study aims to investigate the potential of Facebook as an English language learning tool in Malaysia. It employs both qualitative and quantitative measures in order to analyze the extent of construction of knowledge on the postings on the Facebook walls. Preliminary findings reveal that FB could indeed be an online tool that trigger reflective thinking, construct knowledge and consequently enhance learning.